CHAIN LADDER METHOD FOR RUN-OFF TRIANGLE NUMBER OF REPORTED CLAIMS AND AGGREGATE PAID CLAIMS DATA - Kaisar Malik, Muhammad
The Chain Ladder Method (CLM) is an estimation method which can be used to estimate the outstanding claims liability of the Incurred But Not Reported (IBNR) and the Reported But Not Settled (RBNS) claims in a longtail insurance business applied to a data set recorded in a run-off triangle format. CLM does not use any probability distribution assumptions for the data analyzed. In this Final Project, the Chain Ladder Method is applied to runoff triangles of Incremental Number of Reported Claims and Incremental Aggregate Paid Claims data to estimate the total number of claims to be reported and the total amount of claims to be paid in the future by an insurance company. In addition, a measure of the uncertainty of the estimation is also calculated, namely the prediction error of the estimate obtained by CLM.